Factfulness: Ten Reasons We're Wrong About the World - and Why Things Are Better Than You Think - Hans Rosling; Anna Rosling Rönnlund; Ola Rosling (New York Flatiron Books, 2018)
When asked simple questions about global trends-what percentage of the world's population live in poverty; why the world's population is increasing; how many girls finish school-we systematically get the answers wrong. So wrong that a chimpanzee choosing answers at random will consistently outguess teachers, journalists, Nobel laureates, and investment bankers. In Factfulness, Professor of International Health and global TED phenomenon Hans Rosling, together with his two long-time collaborators, Anna and Ola, offers a radical new explanation of why this happens. They reveal the ten instincts that distort our perspective-from our tendency to divide the world into two camps (usually some version of us and them) to the way we consume media (where fear rules) to how we perceive progress (believing that most things are getting worse). Our problem is that we don't know what we don't know, and even our guesses are informed by unconscious and predictable biases. It turns out that the world, for all its imperfections, is in a much better state than we might think. That doesn't mean there aren't real concerns. But when we worry about everything all the time instead of embracing a worldview based on facts, we can lose our ability to focus on the things that threaten us most. Inspiring and revelatory, filled with lively anecdotes and moving stories, Factfulness is an urgent and essential book that will change the way you see the world and empower you to respond to the crises and opportunities of the future.
Keywords: Stress management; Nonfiction; Economics; History; Politics; Psychology; Philosophy; Self Help; Sociology; Business